‘The Vaïces that Be Gone’—Origins and Purity: the Dialect Poetry of William Barnes, philologist - Paul Volsik (Cahiers Victoriens et Edouardiens)
This article sees the work of the ‘dialect poet’ William Barnes (1801–86) as an emblematic interaction between a certain sort of Romantic aesthetic and contemporary science. It examines firstly Barnes’s philological studies of dialect in relation to contemporary theories of the origins of language and the language of origins. It concludes with an examination of Barnes’s reinvestment and reinvigoration of the pastoral and the idyll—two ‘original’ forms that recreate a disappearing ‘purer’ and ‘original’ order.